Anomalous Intracranial Venous Drainage Associated with Basal Ganglia Calcification - Chen, Z.; Feng, H.; Zhu, G.; Wu, N.; Lin, J. (American Journal of Neuroradiology, 2007)
SUMMARY: We describe the neuroradiologic findings in a 7-year-old boy with anomalous intracranial venous drainage and cerebral calcification. CT scans demonstrated that his scalp mass was a plexus of scalp veins filled through the emissary foramen, and there were cerebral calcifications. Angiography revealed bilateral sigmoid sinus atresia with most of the intracranial venous drainage via the prominent mastoid emissary veins into dilated scalp vein. The possible relationship between cerebral calcification and anomalous intracranial venous drainage is discussed.